2012
DOI: 10.1364/ol.37.000398
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical fiber sensor based on magnetic fluid

Abstract: A novel magnetic field fiber sensor based on magnetic fluid is proposed. The sensor is configured as a Sagnac interferometer structure with a magnetic fluid film and a section of polarization maintaining fiber inserted into the fiber loop to produce a sinusoidal interference spectrum for measurement. The output interference spectrum is shifted as the change of the applied magnetic field strength with a sensitivity of 16.7 pm/Oe and a resolution of 0.60 Oe. The output optical power is varied with the change of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(65 citation statements)
references
References 13 publications
2
63
0
Order By: Relevance
“…In recent years, some ways have been proposed, such as multimode fiber with sensitive film coating [15], PCF deposited with Terfenol particles [16], and optical fiber in combination with magnetic fluid (MF) [17,18]. MF is one kind of magnetic field-sensitive material and has many attractive magneto-optic properties, for example, birefringence property, Faraday property, and magnetic-induced RI tunability [19][20][21][22]. It becomes one subject of numerous studies to combine MF with optical fiber for the measurement of external magnetic field [23,24] and MF birefringence [25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some ways have been proposed, such as multimode fiber with sensitive film coating [15], PCF deposited with Terfenol particles [16], and optical fiber in combination with magnetic fluid (MF) [17,18]. MF is one kind of magnetic field-sensitive material and has many attractive magneto-optic properties, for example, birefringence property, Faraday property, and magnetic-induced RI tunability [19][20][21][22]. It becomes one subject of numerous studies to combine MF with optical fiber for the measurement of external magnetic field [23,24] and MF birefringence [25].…”
Section: Introductionmentioning
confidence: 99%
“…Intensity-modulated magnetic field sensor based on magnetic fluid and optical fiber gratings Jie Zheng, 1,2,3 Xinyong Dong, 1,3,4,a) Peng Zu, 5 Junhua Ji, 2 Haibin Su, 4 and Perry Ping Shum 2 An intensity-modulated magnetic field sensor based on magnetic fluid and optical fiber gratings is proposed and experimentally demonstrated. The sensor is formed by a tilted-fiber Bragg grating (TFBG) coated by magnetic fluid (MF) and cascaded by a chirped-fiber Bragg grating (CFBG).…”
mentioning
confidence: 99%
“…1,2 Recently, magnetic fluid (MF), as an attractive nano-material with magneto-optical effects including Faraday effect, tunable refractive index, field dependent transmission and birefringence, 3,4 was intensively investigated in magnetic field measurement. [5][6][7][8][9] By taking advantage of the field dependent birefringence of MF, Zu et al reported an optical fiber Sagnac interferometer based magneto-optical fiber sensor. 5 The same group of researchers infiltrated MF into air holes in the cladding of a short length index-guided photonic crystal fiber to convert it into a photonic bandgap fiber with a tunable band gap and measured magnetic field by monitoring the bandgap wavelength.…”
mentioning
confidence: 99%
“…More importantly, the magnetic field sensor has a simple structure with the potential for high sensitivity intensity-modulated magnetic field measurements. Compared with fiber magnetic sensors based on enhanced Bragg grating [15] and other optical fiber sensors based on MF, such as MF infiltrated photonic crystal fibers [16,17], Sagnac interferometers [18], cascaded blazing gratings [19], and fiber tapers [20], the proposed scheme features low cost, easy fabrication, and high sensitivity. The proposed structure has higher sensitivity of 0.097 dB/Oe and modulation depth of 78% compared with the existing magnetic field sensors based on SMS and MF, which are mostly wavelength demodulation, such as the magnetic field sensor with sensing sensitivity of 0.01939 dB/Oe by using a square no-core fiber [12].…”
Section: Introductionmentioning
confidence: 99%